Ultrasonographic images and correspondence with real color sectioned images of the upper limb. - Kim, Seul Ki; Hur, Mi-Sun; Park, Jin Seo (Surgical & Radiologic Anatomy, 2024)
Purpose: For basic training in ultrasonography (US), medical students and residents must learn cross-sectional anatomy. However, the present educational material is not sufficient to learn the sectional anatomy for US. This study aimed to provide a criterion for reading ambiguous structures on US images of upper limb through the sectioned images of Visible Korean. Methods: US images of the right arm of a volunteer were scanned (28 planes). For comparison with US images, the sectioned images of the right upper limb (24 bits color, 0.5 mm intervals, 0.06 mm × 0.06 mm sized pixel) were used. After the volume model was constructed from the sectioned images using MRIcroGL, new sectioned images of 28 planes corresponding to the US images of 28 planes were created by adjusting the slope of the volume model. In all images, the anatomical terms of 59 structures from the shoulder to the fingers were annotated. Results: In the atlas, which consists of 28 sets of US images and sectioned images of various slope planes, 59 structures of the shoulder, arm, elbow, wrist, palm, and fingers were observed in detail. Conclusion: We were able to interpret the ambiguous structures on the US images using the sectioned images with high resolution and actual color. Therefore, to learn the cross-sectional anatomy for US, the sectioned images from the Visible Korean project were deemed to be the suitable data because they contained all human gross anatomical information.